PROSPECTS OF DESIGNING FLEXIBLE BUSINESS MODEL IN TURBULENT TIMES - Amalia DUTU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2014)
The present study aims to analyze the current global context to capture the characteristics of the new type of volatile and turbulent business environment in which companies must operate nowdays and to bring some propositions in order to guide managers in designing or redesigning business models to achieve flexibility. The central message of this paper, that is a point of view one, is that, nowdays but also in the future, business models that are based on strategic, organizational and operational flexibility and on reaction speed will be those who will provide the greatest capacity to respond to change. Even if the international theory provides a multiple perspective analysis of business model concept, still how it can be achieved such flexibility remains an open issue in the academic debate, but also in the practice of companies. Thus, the paper contains some propositions in order to guide managers in the process of designing or redesigning the business model.